Mode of Delivery and Unplanned Cesarean: Differences in Rates and Indication by Race, Ethnicity, and Sociodemographic Characteristics - Williams, Alexandria; Little, Sarah E.; Bryant, Allison S.; Smith, Nicole A. (American Journal of Perinatology, 2022)
Objective We aimed to examine the relationship of sociodemographic variables with racial/ethnic disparities in unplanned cesarean births in a large academic hospital system. Secondarily, we investigated the relationship of these variables with differences in cesarean delivery indication, cesarean delivery timing, length of second stage and operative delivery.Study Design We conducted a retrospective cohort study of births >34 weeks between 2017 and 2019. Our primary outcome was unplanned cesarean delivery after a trial of labor. Multiple gestations, vaginal birth after cesarean, elective repeat or primary cesarean delivery, and contraindications for vaginal delivery were excluded. Associations between mode of delivery and patient characteristics were assessed using Chi-square, Fisher exact tests, or t-tests. Odds ratios were estimated by multivariate logistic regression. Goodness of fit was assessed with Hosmer Lemeshow test.Results Among 18,946 deliveries, the rate of cesarean delivery was 14.8% overall and 21.3% in nulliparous patients. After adjustment for age, body mass index (BMI), and parity, women of Black and Asian races had significantly increased odds of unplanned cesarean delivery; 1.69 (95% CI: 1.45,1.96) and 1.23 (1.08, 1.40), respectively. Single Hispanic women had adjusted odds of 1.65 (1.08, 2.54). Single women had increased adjusted odds of cesarean delivery of 1.18, (1.05, 1.31). Fetal intolerance was the indication for 39% (613) of cesarean deliveries among White women as compared to 63% (231) of Black women and 49% (71) of Hispanic women (p <0.001).Conclusion Rates of unplanned cesarean delivery were significantly higher in Black and Asian compared to White women, even after adjustment for age, BMI, parity, and zip code income strata, and rates of unplanned cesarean delivery were higher for Hispanic women self-identifying as single. Racial and ethnic differences were seen in cesarean delivery indications and operative vaginal deliveries. Future work is urgently needed to better understand differences in provider care or patient attributes, and potential provider bias, that may contribute to these findings.Key Points
Keywords: racial disparities; ethnic disparities; pregnancy; zip code income strata; provider bias; non-reassuring fetal status; labor dystocia; cesarean; operative vaginal delivery; equity